From awareness to action: Strategies for improving halal standards in Korean Noodles and Cosmetic Industry - Anindya, Farah; Maulana, Muhammad Ilham Rizky; Najla, Nailun; Tomabilang, Abdul Javher I.; Hidayati, Nurul; Ruslan, Mohd. Firdaus (Halal Studies and Society, 2025)
The global halal market is experiencing rapid growth, projected to reach US$ 4,569.69 billion by 2030. However, maintaining the standards is a major problem, particularly for Korean instant noodles and cosmetic products. Therefore, this research aimed to examine the critical need for improved quality management and compliance in halal food and cosmetic supply chains Issues such as lack of consumer awareness regarding halal labelling and contamination of products with non-halal or hazardous substances are discussed. Several solutions were proposed to address the challenges, including comprehensive halal standard education, internal training programs, and international cooperation for standardization. The results showed that there are several importance of regular and inclusive employee training, recognition strategies, and implementation of halal traceability systems. Additionally, the significance of government agencies and businesses from different countries was emphasized. This cooperation created consistent halal rules expected to be followed on a global basis. By integrating the strategies, manufacturers prevented contamination, ensured adherence to halal standards, and rebuilt consumer trust. Moreover, multi-faceted methods including education, technological advancements, and enhanced regulatory oversight were crucial for maintaining the integrity of halal industry and meeting growing global demand.